USING NONFINANCIAL MEASURES TO IMPROVE FRAUD RISK ASSESSMENTS: OPPORTUNITIES AND LIMITATIONS - Špiler, Marko; Bogojević Arsić, Vesna; Knežević, Snežana (International Journal of Economic Practice and Policy, 2024)
Previous research indicates a growing need to address the issue of fraudulent financial research. In addition to financial measures, non-financial measures are those that should be considered in the process of measuring the economic performance of the company. This research points to the importance of an integrated way of measuring the financial performance of a company in assessing the risk of fraud, which implies the application of non-financial performance measures together with financial ones. If there is a difference between non-financial measures and financial performance, this may be a warning sign that there may be a risk of fraud. Research on the application of non-financial measures in improving the risk assessment of fraud is scarce when looking at the Serbian context. Therefore, this research will add value to the existing literature on fraud risk management in financial statements.